Thermoelectric Skutterudite/oxide nanocomposites: Effective decoupling of electrical and thermal conductivity by functional interfaces. (January 2017) - Moure, A.; Rull-Bravo, M.; Abad, B.; Del Campo, A.; Rojo, Miguel Muñoz; Aguirre, M.H.; Jacquot, A.; Fernandez, J.F.; Martin-Gonzalez, M.
Abstract: Nanocomposites that combine percolated nano-CoSb3 semiconductors with isolated nano-oxide clusters are shown as an effective approach to decouple electrical and thermal conductivity in thermoelectric applications through the formation of functional interfaces. This type of decoupling is very important to increase the Figure of Merit ( zT ) of thermoelectrics and it is one of the greatest challenges searched by the community. We carry out an innovative synthesis of Skutterudite/oxide nanocomposites in air by high energy milling and sintering by Spark Plasma Sintering, where functional interfaces are developed in situ . A confocal Raman Microscopy study evidences unequivocally the appearance of a space charge layer at the Skutterudite/oxide interfaces characterized by a crystal lattice softening and a surprising enhanced Raman signal. The functional interfaces act as highly effective phonon scattering and trapping centers that highly reduce the thermal conductivity, while a high electrical conductivity is achieved by selective doping the Skutterudite phase. This approach leads to Figures of Merit ca. 1 for Te-doped CoSb3 . This work opens up new possibilities for the facile, large scale synthesis of well performing thermoelectric materials for medium range temperatures applications. Graphical abstract: Highlights: High energy milling in air + SPS lead to thermoelectric CoSb3 -oxide nanocomposites. Electrical and thermal conductivity decoupling leads to a high increase of zT. Functional interfaces with space charge layers give new phonon scattering mechanisms. RCM is first time used to study structural and functional properties simultaneously.